IMAGENS E IDEOLOGIA NAS CUNHAGENS DE TEODÓSIO I - Machado, Carlos Augusto Ribeiro (PHOÎNIX, 2020)
Historians of the Later Roman Empire have always been concerned with the Emperor 's image and representations. One problem with this is that many of these historians have often confused the imperial image with the extent of the imperial power. It is the aim of this article to ask some questions and advance some objections to this commonly held opinion, taking the Theodosian mints at the Museu Historic° Nacional (RJ) as evidence.